Mass/Count Variation: A Mereological, Two-Dimensional Semantics - Peter R Sutton; Hana Filip (Baltic International Yearbook of Cognition, Logic and Communication, 2016)
We argue that two types of context are central to grounding the semantics for the mass/count distinction. We combine and develop the accounts of Rothstein (2010) and Landman (2011), which emphasize (non-)overlap at a context. We also adopt some parts of Chierchia’s (2010) account which uses precisifying contexts. We unite these strands in a two-dimensional semantics that covers a wide range of the puzzling variation data in mass/count lexicalization. Most importantly, it predicts where we should expect to find such variation for some classes of nouns but not for others, and also explains why.
Keywords: mass/count distinction; two-dimensional semantics; nouns; counting; context